Affecting others: social appraisal and emotion contagion in everyday decision making. - Parkinson, B; Simons, G (SAGE Publications, 2009)
In a diary study of interpersonal affect transfer, 41 participants reported on decisions involving other people over 3 weeks. Reported anxiety and excitement were reliably related to the perceived anxiety and excitement of another person who was present during decision making. Risk and importance appraisals partially mediated effects of other's anxiety on own anxiety as predicted by social appraisal theory. However, other's emotion remained a significant independent predictor of own emotion after controlling for appraisals, supporting the additional impact of more direct forms of affect transfer such as emotion contagion. Significant affect-transfer effects remained even after controlling for participants' perceptions of the other's emotion in addition to all measured appraisals, confirming that affect transfer does not require explicit registration of someone else's feelings. This research provides some of the clearest evidence for the operation of both social appraisal and automatic affect transfer in everyday social life.